2007
DOI: 10.1158/1535-7163.mct-06-0728
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent roles of mutant B-Raf signaling in melanoma and colorectal carcinoma cell growth

Abstract: Mutational activation of Ras and a key downstream effector of Ras, the B-Raf serine/threonine kinase, has been observed in melanomas and colorectal carcinomas. These observations suggest that inhibition of B-Raf activation of mitogen-activated protein kinase (MAPK)/ extracellular signal-regulated kinase kinase (MEK) and the extracellular signal-regulated kinase MAPK cascade may be an effective approach for the treatment of RAS and B-RAF mutation-positive melanomas and colon carcinomas. Although recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
(45 reference statements)
2
21
0
Order By: Relevance
“…In consistence with the aforementioned biochemical assay results, compound 9d exerted high potencies over the cell lines overexpressing mutant BRAF V600E like COLO 205 and HT29 colon cancer cell lines [40], and MALME-3M [40], SK-MEL-28 [41], SK-MEL-5 [41], and UACC-62 [42] melanoma cell lines. C-RAF is commonly over-expressed in the absence of oncogenic mutations in 50% of RCC (50%) [43], and is associated with poor prognosis in ovarian cancer [44].…”
Section: In Vitro Kinase Screeningsupporting
confidence: 64%
“…In consistence with the aforementioned biochemical assay results, compound 9d exerted high potencies over the cell lines overexpressing mutant BRAF V600E like COLO 205 and HT29 colon cancer cell lines [40], and MALME-3M [40], SK-MEL-28 [41], SK-MEL-5 [41], and UACC-62 [42] melanoma cell lines. C-RAF is commonly over-expressed in the absence of oncogenic mutations in 50% of RCC (50%) [43], and is associated with poor prognosis in ovarian cancer [44].…”
Section: In Vitro Kinase Screeningsupporting
confidence: 64%
“…We also transfected melanoma MMRU, A375, MMLH, SK-mel-3, SK-mel-28, SK-mel-31 and SK-mel-93 cells with EIF5A2 overexpression vector and found that cell invasion in these cell lines increased significantly compared with the vector control (Figure 4B and Supplementary Figures S5B–F and S6B, respectively). Out of these cell lines, MMRU (unpublished sequencing data from our lab), A375 (Chen et al , 2012a), SK-mel-28 and SK-mel-3 (Hao et al , 2007) carry BRAFV600E mutation and SK-mel-31 (Chow et al , 2012) carries NRASQ61K mutation. As MMP-2 was shown to have a crucial role in cell invasion (Vaisanen et al , 1996; Li et al , 2008), we then carried out the zymography assay to compare the activity of MMP-2 in EIF5A2-KD- or EIF5A2-overexpressing MMRU cells compared with respective controls.…”
Section: Resultsmentioning
confidence: 99%
“…However, as far as we are aware, no previous study has compared sorafenib sensitivity among a panel of tumor cell lines of different KRAS mutational status. We have now evaluated the effects of sorafenib on the growth of NSCLC cells harboring wild-type or mutant forms of KRAS with two different assay systems, the MTT assay and anchorage-independent colony formation assay, given that previous studies have revealed differences in the sensitivity of cells to tested drugs between these two assay systems (29). The IC 50 values for inhibition of cell growth by sorafenib in these assays have generally been found to be well below 15 Amol/L, the maximum achievable plasma concentration of this drug (17).…”
Section: Discussionmentioning
confidence: 99%